Cardiomyocyte Maturation Requires TLR3 Activated Nuclear Factor Kappa B. (22nd April 2018) - Hodgkinson, Conrad P.; Pratt, Richard E.; Kirste, Imke; Dal‐Pra, Sophie; Cooke, John P.; Dzau, Victor J.
Abstract: The process by which committed precursors mature into cardiomyocytes is poorly understood. We found that TLR3 inhibition blocked cardiomyocyte maturation; precursor cells committed to the cardiomyocyte lineage failed to express maturation genes and sarcomeres did not develop. Using various approaches, we found that the effects of TLR3 upon cardiomyocyte maturation were dependent upon the RelA subunit of nuclear factor kappa B (NFκB). Importantly, under conditions that promote the development of mature cardiomyocytes NFκB became significantly enriched at the promoters of cardiomyocyte maturation genes. Furthermore, activation of the TLR3‐NFκB pathway enhanced cardiomyocyte maturation. This study, therefore, demonstrates that the TLR3‐NFκB pathway is necessary for the maturation of committed precursors into mature cardiomyocytes. Stem Cells 2018;36:1198–1209 Abstract : Activation of TLR3 enhances direct cardiac reprogramming.